Development Of I-O Card For Pc By Using Microchip Via Rs232 Port And Usb Port - Yeoh, Hooi Liang (Universiti Sains Malaysia, 2017)
The communication between the PC and I/O card which able to control the output signal to machine and read the input signal from machines. Communication is one of the important part in the industrial manufacturing process. There are many types of ports which can be used to communicate with the PC. For this project, the USB and RS232 ports are used to enable the PC to communicate with I/O card. The schematic part need to focus the part of the I/O pins. The voltage signal levels input are higher than the voltage signal levels that can be supported by the I/O card. The optocouplers can be used for switch on the high voltage signal levels output. The high voltage signal levels from the machines will switch on the low signal levels input then send to PIC18 microcontroller. The higher voltage signal levels can between 5V and 24V and the lower signal levels only cannot higher than 0.8V. The microcontroller that used in this project for control the communication of I/O card with the PC is PIC18 microcontroller. The skill of drawing the PCB layout needed in this project. Troubleshoot process need to carry on and avoid the short circuit. PIC18 microcontroller is used need the programming language knowledge to control the system of the communication. PC able to read the input that sent from the machines or sensors, the PC need to set the status of the output. The result will show as the verification of I/O card with PC communication. There are different applications used to test the I/O pins can send and read signal correctly.